2013 10th IEEE International Conference and Workshops on Automatic Face and Gesture Recognition (FG) 2013
DOI: 10.1109/fg.2013.6553775
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual effects of damped and exaggerated facial motion in animated characters

Abstract: Abstract-Common guidelines followed in the animation community include the idea that cartoon characters should be exaggerated to better convey emotion and intent, whereas more realistic characters should have "matching" realistic motion. We investigated the effects of rendering style and amount of facial motion on perceptions of character likeability, intelligence, and extraversion. We used cartoon and more realistic-looking characters that were animated with tracked actor motion. The motion was exaggerated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…In this paper, we examine whether the perceptual effects found in our prior work [20] are applicable when people ac tively interact with an animated avatar rather than passively observe a character. Although we predict that the facial mo tion magnitude of an interactive animated avatar will influ ence participants' judgments, other research suggests that other personality cues may override the effect of facial motion magnitude.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In this paper, we examine whether the perceptual effects found in our prior work [20] are applicable when people ac tively interact with an animated avatar rather than passively observe a character. Although we predict that the facial mo tion magnitude of an interactive animated avatar will influ ence participants' judgments, other research suggests that other personality cues may override the effect of facial motion magnitude.…”
Section: Introductionmentioning
confidence: 95%
“…In a prior experiment using cartoon and comparatively re alistic animated characters [20], we measured viewers' per ceptions of the characters' social traits, such as extrover sion, warmth, and competence. The characters exhibited damped, normal, or exaggerated facial motion while deliv ering a monologue regarding a personal experience.…”
Section: Introductionmentioning
confidence: 99%
“…We aimed for our CG characters to be of similar quality. However, previous research has shown that small differences in rendering styles can influence perceptual judgments of CG characters [McDonnell et al 2012;Hyde et al 2013]. SD, the female character, had fewer wrinkles, leading to a smoother face appearance.…”
Section: Discussionmentioning
confidence: 94%
“…Hyde et al [13] studied the e ects of damped and exaggerated facial motion in virtual characters rendered realistically or in a cartoon style and found that realistically rendered characters bene ted from exaggerated motion and cartoon rendered characters bene ted from damped. In a study by [21], images of illustrated characters showing emotions of fear and anger were manipulated to congruent and incongruent stimuli by exchanging the faces in the images.…”
Section: Related Workmentioning
confidence: 99%